PENGARUH PERGAULAN TERHADAP AKHLAK SISWA DI MTs MATHLA'UL ANWAR TUYAU - Rasidah, Jamiatur; Dzaky, Ahmad; Syahrani, Syahrani (STIT Ibnu Rusyd Tanah Grogot, 2023)
Many students associate with using harsh words and bad behavior such as bullying friends, teasing friends, disturbing and even fighting with friends so that it raises bad morals in students. This study aims to determine whether there is social influence on student morals at MTs Mathla'ul Anwar Tuyau. The research method used is a quantitative method. Data collection techniques in this study were through observation, interviews, documentaries and questionnaires. The data is processed using editing, coding, scoring, tabulating and data interpretation techniques and using quantitative descriptive research methods using the product moment correlation formula. Based on the results of the research, it was found that the effect of association on student morals at MTs Mathla'ul Anwar Tuyau based on the results of data analysis was 0.1361, which was in the interval 0.00 – 0.20 with an interpretation between the X and Y variables, there was indeed a correlation. however, the correlation is so weak or so low that it is ignored. Thus there is no significant influence between associations on student morals at MTs Mathla'ul Anwar Tuyau, this is indicated by the rh value (0.1361) less than the rt level of 5% (0.2012) and 1% (0.2816) and the hypothesis is rejected.